Bloodstream infections in different stage of reconstitution after first allogeneic hematopoietic stem cell transplantation - M. I. Akhmedov; G. A. Klyasova; E. N. Parovichnikova; L. A. Kuzmina; A. V. Fedorova; V. A. Vasil’eva; M. Yu. Drokov; S. M. Kulikov; V. G. Savchenko (Онкогематология, 2022)
Background. Bloodstream infections (BSI) are common after allogeneic hematopoietic stem cell transplantation (allo-HSCT). The objective of study was to analyze pre- and post-engraftment BSI.Materials and methods. From January 2018 till May 2021242 patients after first allo-HSCT were enrolled in the study. Median age was 35 (17–65) years. The majority of transplants were done for acute leukemias (71.9 %) in remission (91.7 %) with reduced-intensity conditioning regimens (71.5 %) and peripheral blood stem cells (74.4 %) as a graft source.Results. Of 242 patients 95 (39.2 %) developed BSI: 79 (83.2 %) developed 1 BSI episode, 16 (16.8 %) – 2 or more. Overall 113 BSI episodes were registered: 94 (82.7 %) were caused by single microorganism, 19 (17.3 %) were polymicrobial. Probability of pre-engraftment BSI was 31.0 %, post-engraftment – 11.8 %. In total 134 microorganisms were identified: 61.2 % – gram-negative and 38.8 % – gram-positive bacteria. Gram-negative BSI rate was significantly higher during post-engraftment compared to pre-engraftment phase (57.7 % vs. 70.3 %; р = 0.008). Major risk factor for pre-engraftment BSI was mismatched unrelated allo-HSCTs (hazard ratio (HR) 2.55; 95 % confidence interval (CI) 1.32–4.91; р = 0.03), for post-engraftment BSI – secondary poor graft function (HR 21.70; 95 % CI 7.95–59.24; р <0.0001) and graft failure (HR 21.55; 95 % CI 6.27–74.08; р <0.0001), and gut graft-versus-host disease (HR 12.90; 95 % CI 5.77–28.80; р <0.0001). Thirty-day survival after each BSI episode was 90.3 % and was significantly lower in patients with post-engraftment BSI compared to pre-engraftment (71.9 % vs. 97.5 %; р <0.0001).Conclusion. Gram-negative bacteria prevailed in the etiology of BSI. The main risk factors for pre-engraftment BSI was allo-HSCT from mismatched unrelated donors, for post-engraftment BSI – secondary poor graft function and graft failure. Post-engraftment BSI is associated with worse prognosis.